Phenotypic plasticity of two M. oleifera ecotypes from different climatic zones under water stress and re-watering. Issue 1 (13th April 2020) - Brunetti, Cecilia; Gori, Antonella; Moura, Barbara Baesso; Loreto, Francesco; Sebastiani, Federico; Giordani, Edgardo; Ferrini, Francesco
Abstract: Moringa oleifera is a fast-growing hygrophilic tree native to a humid sub-tropical region of India, now widely planted in many regions of the Southern Hemisphere characterized by low soil water availability. The widespread cultivation of this plant worldwide may have led to populations with different physiological and biochemical traits. In this work, the impact of water stress on the physiology and biochemistry of two M. oleifera populations, one from Chaco Paraguayo (PY) and one from Indian Andhra Pradesh (IA) region, was studied in a screenhouse experiment where the water stress treatment was followed by re-watering. Through transcriptome sequencing, 2201 potential genic simple sequence repeats were identified and used to confirm the genetic differentiation of the two populations. Both populations of M. oleifera reduced photosynthesis, water potential, relative water content and growth under drought, compared to control well-watered plants. A complete recovery of photosynthesis after re-watering was observed in both populations, but growth parameters recovered better in PY than in IA plants. During water stress, PY plants accumulated more secondary metabolites, especially β-carotene and phenylpropanoids, than IA plants, but IA plants invested more into xanthophylls and showed a higher de-epoxidation state of xanthophylls cycle that contributed to protect the photosynthetic apparatus. M. oleifera demonstrated a high genetic variability and phenotypic plasticity, which are key factors for adaptation to dry environments. A higher plasticity (e.g. in PY plants adapted to wet environments) will be a useful trait to endure recurrent but brief water stress episodes, whereas long-term investment of resources into secondary metabolism (e.g. in IA plants adapted to drier environments) will be a successful strategy to cope with prolonged periods of drought. This makes M. oleifera an important resource for agro-forestry in a climate change scenario.